2017
DOI: 10.1111/bph.13853
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized low‐density lipoprotein stimulates epithelial sodium channels in endothelial cells of mouse thoracic aorta

Abstract: This article is part of a themed section on Spotlight on Small Molecules in Cardiovascular Diseases. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.8/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Our previous studies have shown that cholesterol elevates intracellular ROS in both lymphocytes and CCD principal cells (Liu, Song, et al, ; Song et al, ). We have also shown that hydrogen peroxide stimulates ENaC in cultured distal nephron cells (Ma, ) and that oxidized LDL significantly increased ENaC activity by elevating intracellular ROS (Liang et al, ). In this study, we show that increased intracellular cholesterol causes ROS probably by increasing 4‐HNE in ABCA1 KO mice.…”
Section: Discussionmentioning
confidence: 92%
“…Our previous studies have shown that cholesterol elevates intracellular ROS in both lymphocytes and CCD principal cells (Liu, Song, et al, ; Song et al, ). We have also shown that hydrogen peroxide stimulates ENaC in cultured distal nephron cells (Ma, ) and that oxidized LDL significantly increased ENaC activity by elevating intracellular ROS (Liang et al, ). In this study, we show that increased intracellular cholesterol causes ROS probably by increasing 4‐HNE in ABCA1 KO mice.…”
Section: Discussionmentioning
confidence: 92%
“…Not only aldosterone, but also Ox-LDL (oxidized low-density lipoprotein) has been found to stimulate ENaC activity in endothelial cells. This mechanism involves LOX-1 receptor (lectin-like ox-LDL receptor-1)-mediated activation of NADPH oxidase (nicotinamide adenine dinucleotide phosphate-oxidase) and the inhibition of ENaC protects the endothelium from ox-LDL-induced dysfunction ( Liang et al, 2017 ). Interestingly, ENaCs are sensitive to stretch pressure and shear stress and responded to shear stress by increasing the Na (+) influx that could also contribute to endothelium dysfunction ( Guo et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying mechanism remains unclear. We and other investigators have shown that ENaC is expressed in the endothelial cells and mediates vascular tension (Jeggle et al, 2013;Liang et al, 2018). Therefore, CsA may not only stimulate ENaC in the kidney but also activate ENaC in the endothelial cells, to increase blood pressure.…”
Section: Discussionmentioning
confidence: 91%
“…Since Cho-rich membrane microdomains are required for the assembly and activity of NADPH oxidase ( Vilhardt and van Deurs, 2004 ; Rao Malla et al, 2010 ), our data suggest that CsA-induced Cho accumulation in principal cells may account for activation of NADPH oxidase and the followed elevation of intracellular ROS. Our previous studies show that palmitate stimulates ENaC by increasing ROS in cultured distal nephron cells ( Wang et al, 2018 ) and that oxidized LDL also stimulates ENaC by increasing intracellular ROS ( Liang et al, 2018 ). In this study, we show that CsA increases ROS probably by increasing the expression of subunit of NADPH oxidase, p47 phox .…”
Section: Discussionmentioning
confidence: 99%